ATM Technology Prospects: A Review (International Journal of Engineering and Computer Science, 2014)
The implementation of ATM (Asynchronous Transfer Mode) is needed for quick access to web-based applications and real-time delivery of multimedia transmissions on an integrated network infrastructure. ATM is a high-performance technology that provides bandwidth on-demand for broadband transmissions and hence supports seamless transport of full-motion video, audio, data, animations and still images in local and wider area environments on different data rates. Asynchronous transfer mode (ATM) also known as Cell Relay is a cell-oriented switching and multiplexing technology. It uses fixed-length packets to carry different types of traffic and employs the asynchronous time division multiplexing. This feature will likely to have broad positive impacts on  revenue opportunities since multiple types of services like- high speed local-area network (LAN) interconnection, voice, video, and future multimedia applications in business and residential markets will then depend on ATM technology in both short as well as long term of time. ATM will not only reduce the infrastructure costs through efficient bandwidth management, operational simplicity and usage of existing networks but also it will diminish the unacceptable time delay between packets.